Dimensional Investigation Of Corrugated Steel Silo With 4650 Tons Storage Capacity. (March 2019) - Widyanto, Susilo Adi; Sukamta,; Suprihanto, Agus; Paryanto,; Yurianto,
Abstract: One of the failure modes of the silo structure is tearing due to the slope of the silo, which is caused by radial and gravitational forces. Therefore, dimensional measurement of silo becomes a major aspect for predicting the silo conditions. This paper presents a dimensional measurement of silos use a portable laser distance meter (LDM). Measurement process were performed on silo with a capacity of 4650 tons of grain with diameter 19000 mm and height 20000 mm. The silo walls use corrugated steel panels that joined by bolt connection. Measured steps are: LDM calibration, vertical wall measurement, plotting data and then interpretation of silo roundness condition. The results show that at 0% loading capacity, the diameter of the silo at highest position is smaller than the lowest position. However, at 100% of loading capacity deformation of the wall of the silo is occurred. At a height of 18 mm, the maximum displacement of walls reaches 300 mm.